Measuring Historical Thinking Ability: A Quantitative Study of Students on The Indonesia-Malaysia Border, Sambas Regency, West Kalimantan - Firmansyah, Haris; Putri, Astrini Eka (Yupa: Historical Studies Journal, 2025)
This study aims to describe the process of history teaching and the HT skills of high school students in the Indonesia-Malaysia border region. The method used is quantitative with a descriptive case study approach. Data were collected through questionnaires, observations, and documentation, with the research subjects being Social Studies students at SMA Negeri 1 Sajingan Besar, Sambas, West Kalimantan. The data were analyzed descriptively using simple statistics. The history learning process in the border area is running well, with teachers using local content and engaging teaching media. Students showed a reasonably good level of HT skills, although there are still some gaps in discussion activities and report writing skills. Sequential and contextual history teaching helps students understand cause-and-effect relationships between events.